The challenges of wheelchair prescription assessment on appropriateness and practical design for Malaysian users / Ruwaidy Mat Rasul - Mat Rasul, Ruwaidy (Institute of Graduate Studies, UiTM, 2017)
The wheelchair has become a main assistive tool for a person with mobility impairment in assisting them to perform daily life activities, and thus maintaining their quality of life. For this reason, the wheelchair was created in various types of design to fulfil the specific categories of mobility. Therefore with a good understanding of their nature mobility, the wheelchair is created to pursue something that reflects their needs. This will then affect the user’s abilities and function. Without a correct wheelchair prescription, the users will suffer in term of ability functionality, physical deformities and overall, affect the user’s quality of life. One of constrain faced by the wheelchair users, is the need to purchase their own wheelchair. Further to that, the unnecessarily expensive price for a wheelchair creates an additional budget constrain towards the wheelchair users. For this reason, the related government agencies and private organizations offered several schemes to the eligible applicants in obtaining a free wheelchair. However, most of the applicants and recipients didn’t receive the exact materials as what was prescribed according to their needs and requirements, in the given schemes. Therefore this research tend to investigate further their needs, constrains, assessment process and satisfaction. As a result to that, the suggestion and recommendation will be proposed in tackling the issues raised. The quantitative approach is used in the first phase to reveal what are the real issues behind the wheelchair users. Following that, the generalizations of ideas can be made…